Innovative Possibilities of the European Medium-Sized Countries – Conclusions for Bulgaria - Kerchev, Krasimir (Research Papers, 2011)
The current research paper is a study of the innovative possibilities in the European medium-sized countries – Austria, Belgium, Bulgaria, Denmark, Ireland, the Netherlands, Norway, Finland, Switzerland and Sweden. Against this background, it is a comparison with the level of the European Union, the United States and Japan.The study is structured in three parts with an introduction and conclusion.In the first part is present general requisites and preconditions for the creation of an environment for innovation activity at the entrance of the national innovation system and provide positive results and outcome of its functioning in the exit.In the second part analyzes the innovation activity of the European medium-sized countries on the indicators grouped into three pillars – Enablers, Firm activities and Outputs in the Summary Innovation Index. Data for Bulgaria are outlined separately in order to identify those preconditions in the country in comparison with other countries.In the third part compares the innovation activity of the European medium-sized countries with that of the European Union, the United States and Japan on dynamic of innovation activity, innovation gap and growth/decline in innovation. Makes a classification, clustering and positioning of the parties to the innovative possibilities. To display the status and location of Bulgaria, the indicators for the country are drawn independently.Survey results show that the European medium-sized countries involved have created conditions for higher innovation activity and the leading edge in innovation possibilities. On the basis of the displayed trends shown, paper ends with a conclusion in which make findings and recommendations for possible directions in State innovation policy of Bulgaria in order to overcome the lag in innovation in the economy of other countries.